Emerging adulthood: prediction by markers of adulthood and associations with health in a Russian sample - Mikhaylova, Oxana (Frontiers in Public Health, 2025)
IntroductionMarkers of the transition from adolescence to adulthood are changing in many countries, with traditional milestones such as marriage, parenthood, and financial independence becoming less central. This study investigates how changes in the emerging adulthood mindset relate to various maturity markers—including relationship status, parenthood, employment, education, material well-being, independent living—as well as subjective health indicators.MethodsData were collected from two consecutive waves (2021 and 2022) of the Trajectories in Education and Careers (TrEC) longitudinal study, involving 2,663 Russian young adults aged 24 to 28 (54.5% female). Correlation, t-test, ANOVA, and regression analyses were used to assess associations between changes in IDEA (Inventory of the Dimensions of Emerging Adulthood) scores and changes in maturity markers and health indicators over a one-year period.ResultsThe analyses revealed that having children and higher material well-being were significantly associated with changes in the emerging adulthood mindset. In contrast, other traditional markers—such as relationship status, education, and living with parents—were not significantly associated. Several health indicators, including subjective health status, healthy lifestyle, prior mental health specialist consultation, and anxiety, were also linked to changes in the emerging adulthood mindset.DiscussionThese findings indicate that not all traditional markers of adulthood are relevant for emerging adults today. The results highlight the growing importance of health-related factors in understanding the transition to adulthood, suggesting a shift in the criteria that define this life stage.